Fitting It All In? A Census of Undergraduate Ethics and Leadership Courses in Accredited U.S. Journalism and Mass Communication Programs. (September 2019) - Mills, Andrew; Sanders, Amy Kristin; Hussain, Shakir Shahid
As journalism and mass communication programs struggle to help prepare their students for the unknown digital future, many are answering the industry call to inject curricula with the instruction of digital skills. However, this likely comes at the cost of teaching long-standing conceptual courses, including media ethics, or introducing new ones, including media leadership. Although university administrators are likely to say their curricula adequately address these issues, the reality is that they may not. This study analyzed undergraduate degree requirements for all accredited U.S.-based journalism and mass communication degree programs ( N = 119) to evaluate the course offerings in ethics and leadership.